If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 5) + 2x + -2 = 26 Reorder the terms: 7(5 + x) + 2x + -2 = 26 (5 * 7 + x * 7) + 2x + -2 = 26 (35 + 7x) + 2x + -2 = 26 Reorder the terms: 35 + -2 + 7x + 2x = 26 Combine like terms: 35 + -2 = 33 33 + 7x + 2x = 26 Combine like terms: 7x + 2x = 9x 33 + 9x = 26 Solving 33 + 9x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + 9x = 26 + -33 Combine like terms: 33 + -33 = 0 0 + 9x = 26 + -33 9x = 26 + -33 Combine like terms: 26 + -33 = -7 9x = -7 Divide each side by '9'. x = -0.7777777778 Simplifying x = -0.7777777778
| 9c=10c+7 | | -10x-41+7x+3=7x+12 | | 56n^2-40n=0 | | 12.69=2g+3.97 | | 4/24x^3y^2,11/6x^3y | | 24v^2+152v+160=0 | | x+x+1.13x+0.16=10.76 | | 3a+4=2+18 | | 6v^2+39v+63=0 | | X^4-8x^3+35x^2-10x+27=0 | | 10x^3+x-1=0 | | (x)(x+3)=28 | | -5x+21=5x+2+6x-13 | | 4u=28 | | 7+3x+6=7x-5+5x | | 12x-40+7x+23=90 | | 12x-4x+136=12x+76 | | 21p^2-49p-42=0 | | x-8=90 | | 3(8+1)+6= | | 6.9=8.4-0.5x | | (x^2+x-20)(14x^2-3x-2)=0 | | -2(3k)=15 | | 6.9=8.4-0.5 | | 2y-x=-20 | | 3(10+1)+6= | | 7w+20=11w-20 | | f(x)=(2/3*3.1416x^6)^2 | | 51a^3-34a= | | 20p=-14+19p | | 4n^2+20n-56=0 | | -2x-5x-8=3x-8 |